Upper Canadians and Their Guns: An exploration via country store accounts (1808-61) - McCalla, Douglas (Ontario History)

(untitled) (The Ontario Historical Society, 2005)
The gun is an essential part of our images of pioneering and pioneer manliness. We picture the pioneer family surrounded by forest, its men and boys using guns for protection from threatening predators, for sport, and for hunting, as the family relied on an abundance of game to supplement its initially limited farm produce. On the other hand, descriptions of Upper Canadian militia musters and of the 1837 Rebellion suggest that many rural Upper Canadians had only limited experience in using guns or did not have usable firearms at all.Framed by these contrasting images, this paper seeks to read a sample of country store charge accounts of some ordinary Upper Canadian farmers and artisans (in Leeds and Peterborough counties) for indications of gun use. Based on the frequency and scale of purchases of gunpowder and shot, it seems that after the earliest years, the militia-based image is the more likely one. For many, perhaps most, rural Upper Canadians, firing a gun was an occasional more than a routine part of rural life. Among the reasons: a lack of time.